Selective Crystallisation of Carbamazepine Polymorphs on Differing Surface Properties - Yang,H; Song,C; lim,Y; chen,W; Heng,JYY (CrystEngComm, 2017)
Surface-induced nucleation of carbamazepine (CBZ) in ethanol was investigated with different surface materials: glass, polytetrafluoroethylene (PTFE) and tin. The introduction of foreign surfaces with different areas and surface chemistries into the solution has an impact on the crystal morphology and polymorphic form (Form II or III). With an increase in supersaturation, a higher possibility of crystallisation of CBZ metastable Form II was observed, as expected. Increasing the number of inserts resulted in a direct increase in the surface area available for heterogeneous nucleation. The increase in surface area resulted in the greater possibility of obtaining the metastable Form II of CBZ. The stable Form III preferred to nucleate on tin rather than on glass and PTFE. The results indicate that the two different polymorphs of CBZ can be selectively crystallised out from solution with the aid of a foreign surface. The kinetic mechanism of heterogeneous nucleation of the different polymorphs induced by foreign surfaces was discussed. The potential applications will be used to control and design the crystallisation process.